UV/TiO2 photocatalysis as post-treatment of anaerobic membrane bioreactor effluent for reuse - Huang, Yu; Jeffrey, Paul; Pidou, Marc (Elsevier, 2024)
Advanced oxidation processes have been widely applied as a post-treatment solution to remove residual organic compounds in water reuse schemes. However, UV/TiO2 photocatalysis, which provides a sustainable option with no continuous chemical addition, has very rarely been studied to treat anaerobically treated effluents. In the current study, the removal of organics and nutrients from an anaerobic membrane bioreactor (AnMBR) effluent is evaluated during adsorption and photocatalysis processes under various conditions of TiO2 dose and UV intensity and compared to the effluent from an aerobic membrane bioreactor (AeMBR). The sequence for preferential adsorption on TiO2 was found to be phosphorus, inorganic carbon and then ammonia/organic carbon were found. The competing effect between the organics and nutrients, along with the low UV transmission efficiency caused by the need for high doses of TiO2, ultimately compromise the organic removal efficiency in the AnMBR permeate. TiO2 dosage was found to have a greater impact than UV intensity on improving the overall removal performance as nutrients are competing for the adsorption site but are not photodegraded. Under the same operational condition, the UV/TiO2 photocatalysis displayed a higher removal efficiency of organic matter and phosphorus in the AeMBR effluent due to a lower initial organics concentration and absence of ammonia as compared to the AnMBR effluent.
Keywords: UV; TiO2; Anaerobic; Membrane bioreactor; Adsorption; Nutrients